2016
DOI: 10.1002/2016gl068177
|View full text |Cite
|
Sign up to set email alerts
|

A Southern Ocean mode of multidecadal variability

Abstract: A 250 year simulation of a strongly eddying global version of the Parallel Ocean Program (POP) model reveals a new mode of intrinsic multidecadal variability, the Southern Ocean Mode (SOM), with a period of 40–50 year. The peak‐to‐peak difference in the global ocean heat content within a multidecadal cycle is up to 60 ZJ. This change results from surface heat flux variations in the South Atlantic and propagation of temperature anomalies along the Antarctic Circumpolar Current and into the Weddell gyre around 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
124
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(137 citation statements)
references
References 53 publications
13
124
0
Order By: Relevance
“…A previous study by Le Bars et al . [] discussed a key role of eddy‐mean flow interaction in generating decadal temperature variation in the South Atlantic, but our CGCM did not show this effect due to insufficient horizontal resolution. Since the decadal variability is generated even without oceanic mesoscale eddies, the role of atmospheric forcing may be significant, but the relative role of atmospheric forcing and oceanic eddies in generating the decadal temperature variability should be investigated by using eddy‐resolving CGCM.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study by Le Bars et al . [] discussed a key role of eddy‐mean flow interaction in generating decadal temperature variation in the South Atlantic, but our CGCM did not show this effect due to insufficient horizontal resolution. Since the decadal variability is generated even without oceanic mesoscale eddies, the role of atmospheric forcing may be significant, but the relative role of atmospheric forcing and oceanic eddies in generating the decadal temperature variability should be investigated by using eddy‐resolving CGCM.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Note that in Le Bars et al . [], the atmospheric forcing used in their OGCM experiment is based on annual cycle of atmospheric variables, so a possible influence of atmospheric interannual‐to‐decadal variability in the South Atlantic remains unclear. Also, the multidecadal variability reproduced in their OGCM has much longer timescale than the observed decadal variability with a period of 20 years, and physical mechanisms behind the eastward propagation of multidecadal temperature variability are not fully examined.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, output from a 326‐year simulation with a strongly eddying (a horizontal grid spacing of 0.1° ) version of the Parallel Ocean Program (POP) revealed multidecadal (40‐ to 50‐year) spatiotemporal variability in the Southern Ocean (Le Bars et al, ), termed the Southern Ocean Mode (SOM). Although the spatial pattern of the SST anomalies spans the full Southern Ocean, large‐scale anomalies occur in the Weddell Sea area.…”
Section: Introductionmentioning
confidence: 99%
“…A first description of the mechanisms of the SOM was presented in Le Bars et al (). It was shown that the changes in overall potential energy (PE) and kinetic energy (KE) in the region south of 30° S (associated with the SOM) could be linked to a dynamical mechanism described by Hogg and Blundell () who used an idealized quasi‐geostrophic model.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, one recent study 18 demonstrated in an eddy-resolving ocean general circulation model (OGCM) that the multi-decadal SST variability in the Atlantic Sector of the Southern Ocean can be generated as an intrinsic ocean variability mode through eddy-mean interaction and propagate eastward along the background eastward current. Since the decadal SST variability generated in the South Atlantic tends to migrate eastward and have potential influences on decadal climate variability in the southern Indian Ocean 14,19 , skillful prediction of the decadal SST variability in the South Atlantic is crucial for that of decadal climate variability in the southern Indian Ocean.…”
Section: Introductionmentioning
confidence: 99%